Three new species of the pill millipede genus Hyleoglomeris Verhoeff, 1910, from northern Thailand (Diplopoda, Glomerida, Glomeridae) - Likhitrakarn, Natdanai; Golovatch, Sergei I.; Panha, Somsak (Zootaxa, 2015)
Seven species of the basically warm temperate to tropical Eurasian genus Hyleoglomeris are currently known from Thailand, including three new ones: H. hongkhraiensis sp. n. and H. aurea sp. n. from Chiang Mai Province, and H. cavicola sp. n. from Sukhothai Province. A new distribution map and a key to all Hyleoglomeris species presently known to occur in Thailand are given.